Characterizing Spatial Diversity of Passive Sampling Sites for Measuring Levels and Trends of Semivolatile Organic Chemicals - Kalina, Jiří; Scheringer, Martin; Borůvková, Jana; Kukučka, Petr; Přibylová, Petra; Sáňka, Ondřej; Melymuk, Lisa; Váňa, Milan; Klánová, Jana (Environmental science & technology, 2018)
Passive air sampling of semivolatile organic compounds (SVOCs) is a relatively inexpensive method that facilitates extensive campaigns with numerous sampling sites. An important question in the design of passive-sampling networks concerns the number and location of samplers. We investigate this question with the example of 17 SVOCs sampled at 14 background sites across the Czech Republic. More than 200 time series (length 5-11 years) were used to characterize SVOC levels and trends in air between 2003 and 2015. Six polychlorinated biphenyls (PCBs), 6 polyaromatic hydrocarbons (PAHs), and 5 organochlorine pesticides (OCPs) at 14 sites were assessed using data from the MONET passive sampling network. Significant decreases were found for most PCBs and OCPs whereas hexachlorobenzene (HCB) and most PAHs showed (mostly insignificant) increases. Spatial variability was rather low for PCBs and OCPs except for dichlorodiphenyltrichloroethane (DDT) and rather high for PAHs. The variability of the SVOC levels and trends depends on characteristics of the sites including their remoteness, landscape, population, and pollution sources. The sites can be grouped in distinct clusters, which helps to identify similar and, thereby, potentially redundant sites. This information is useful when monitoring networks need to be optimized regarding the location and number of sites.
Keywords: Pesticides; polychlorované bifenyly; Česká republika; Polychlorinated Biphenyls; látky znečišťující vzduch; Air Pollutants; chlorované uhlovodíky; Czech Republic; polycyklické aromatické uhlovodíky; pesticidy; Hydrocarbons, Chlorinated; Polycyclic Aromatic Hydrocarbons; Environmental Monitoring; monitorování životního prostředí